HEDGES AND BOOSTERS ON COVID19.GO.ID:A STUDY OF DOUBTS AND CERTAINTY IN EDUCATIONAL CONTENT (HEDGES DAN BOOSTERS DALAM LAMAN COVID19.GO.ID: KAJIAN TENTANG KERAGUAN DAN KEYAKINAN DALAM KONTEN EDUKATIF) - Andwi Sulistiyo; Teguh Setiawan (Metalingua: Jurnal Penelitian Bahasa, 2021)
During the Covid-19 pandemic, many writings with educational content were produced. To state his position on facts or opinions, the writer needs to pay attention to the selection of hedges and boosters in accordance with the context. Based on 420 educational content presented on the Covid19.go.id, this study describes the forms and functions of hedges and boosters. This research was conducted in five steps, namely careful reading, recording the forms on data cards, data categorization, data analysis, and conclusion. The results are as follows. The Covid.19.go.id has more boosters than hedges. The most widely used forms of expression, both hedges and boosters, are epistemic adjectives and adverbs. The functions of hedges in educational content are to show uncertainty, avoid confrontation, show politeness, persuade, and provide alternative choices to readers. Meanwhile, boosters have functions to show a strong commitment, show information reliability, and close opportunities for negotiation between writers and readers.